Examining musical elements in Toy Story soundtrack “You’ve Got a Friend in Me” - Berehme Adyatma Purba; Raditya Alifamughni (Universitas Pendidikan Indonesia, 2023)
Animated comedy and adventure films are highly enjoyable to watch. In addition to being an enjoyable film, it is also suitable for viewers of all ages, ranging from children to adults. Furthermore, films of this genre are often sought after by families seeking weekend entertainment. In addition to being captivating to watch, films in this genre typically aim to impart a moral message. The